Navigating the Cloud: Analysis of Product Deployment Timeline on Cloud Infrastructure for E-Commerce: A Case Study at Company X - Kusuma Asdani; Endroyono Endroyono (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study seeks to analyze the factors affecting the efficiency of product launch timelines within the cloud infrastructure at Company X, which operates in the e-commerce sector. The primary issue identified is the prolonged product launch process, attributed to technical and operational challenges as well as inadequate team coordination. A review of the literature suggests that process automation through tools such as Terraform and Jenkins could enhance launch efficiency. This research utilizes a qualitative approach with thematic analysis to investigate various obstacles, including application compatibility issues, configuration errors, skills deficiencies within the team, and reliance on manual processes.The findings indicate that automation has the potential to reduce launch times by up to 50%, thereby significantly enhancing overall work efficiency. Nevertheless, challenges such as insufficient team training in automation tools and weak interdepartmental coordination were also noted. Recommendations include the implementation of comprehensive automation strategies, the development of training programs to improve team competencies, and the adoption of more effective cost management practices. This study contributes empirical insights within the e-commerce context and presents practical solutions aimed at improving product launch efficiency in cloud infrastructure.